The clearance effect of progressive punching on straight-plate implant quality - Yani Kurniawan; Wina Libyawati; Dede Lia Zariatin (Results in Engineering)
The progressive punch technology application in straight-plate implant manufacturing requires the ideal clearance selection. It aims to produce the quality of straight-plate implants according to implant standards. The clearance selection for the manufacture of straight-plate implants is challenging. It has caused minimal study on the punching process of pure titanium. This study aims to inspect the clearance effect on the straight-plate implant quality. The quality of the straight-plate implants is investigated in terms of the cutting surface, surface roughness, and material hardness. The clearance variations used were 20, 40 and 60 µm. The results showed that increasing clearance caused the cutting surface quality of the straight-plate implant to be worse. It causes reducing in burnish and fracture height, and it causes increasing in rollover and burr height. In addition, increasing clearance also increases the surface roughness and hardness of the cutting surface of the straight-plate implant. The best quality of the straight-plate implants is produced using a clearance of 20 µm. This results in rollover, burnish, and burr heights of approximately 145, 208, and 23 µm, respectively. The surface roughness and hardness of the cutting surface were approximately 0.86 µm and 172 VHN, respectively. The resulting surface roughness is under implant standard on medium roughness (1-2 µm). Progressive punch technology can be used as an alternative process for manufacturing microplate implants.